New Technologies in Improving the Construction Organization of Gas Transmission Networks / Новые технологии в совершенствовании организации строительства магистральных газотранспортных сетей - Tatyana V. Kudryashova / Татьяна В. Кудряшова; Larisa E. Skripkina / Лариса Е. Скрипкина (Beneficium, 2019)
It is well known that Russia is a leading producer and exporter of natural gas. In this regard, it is difficult to overestimate the importance of the development of the domestic gas industry. One of the activities of the gas industry is the construction of gas transmission networks, as well as their repair. During those and other works there are problems that cause disruption of the timing of commissioning of facilities, which negatively affects the financial and image characteristics of enterprises. One of the main directions of solving this problem is the use of new technologies for the construction of gas transmission networks. «Petroholding–St. Petersburg» stock company engaged in construction and repair of gas transmission networks was chosen as the research object. As part of this study, one of the seven sites included in the structure of the enterprise was considered. The study identified a number of causes for the failure of the construction deadlines: high degree of equipment deterioration, lack of automation and mechanization of technological process, lack of clear interaction between the hierarchical structures of the company, etc. Identified problems are not the prerogative of this site, and are systemic to the whole enterprise. In order to address the identified shortcomings in this work, three activities are proposed that will improve theconstruction organization of networks. First of all, this is the replacement of the welding machine, with which manual welding is performed, with a more automated method, which will reduce the time of welding several times. The paper considers two alternative options for replacing manual welding. Secondly, it is the introduction of preventive maintenance of machines, machinery and equipment. Thirdly, establishing communication between the head office and the sites, as well as stimulating the work of staff. These measures will not only increase the efficiency of the company as a whole, but can also be considered as universal for enterprises working in this field. Общеизвестно, что Россия является ведущим производителем и экспортером природного газа. В связи с этим значение развития отечественной газовой отрасли сложно переоценить. Одним из видов деятельности газовой отрасли является возведение магистральных газотранспортных сетей, а также их ремонт. Во время тех и других работ возникают неполадки, которые вызывают срыв сроков введения в эксплуатацию объектов, что негативно сказывается на финансовых и имиджевых характеристиках предприятий. Одним из основных направлений решения данной проблемы является применение новых технологий организации строительства магистральных газотранспортных сетей. В качестве объекта исследования выбрано Акционерное общество «Петрохолдинг–Санкт-Петербург», осуществляющее работы по строительству и ремонту газотранспортных сетей. В рамках данного исследования из семи участков, входящих в структуру предприятия, был рассмотрен один. Исследование позволило выявить ряд причин, вызывающих срывы сроков строительства: высокая степень изношенности оборудования, отсутствие автоматизации и механизации технологического процесса, отсутствие четкого взаимодействия между иерархическими структурами компании и др. Выявленные проблемы не являются прерогативой исключительно данного участка, а носят системный характер для предприятия в целом. С целью устранения выявленных недостатков в рамках данной работы предлагаются три мероприятия, которые позволят усовершенствовать организацию строительства сетей. В первую очередь, это замена сварочного аппарата, с помощью которого производится ручная сварка, на более автоматизированный способ, что позволит сократить сроки проведения сварочных работ в несколько раз. В работе рассмотрены два альтернативных варианта замены ручной сварки. Во-вторых, это внедрение планово-предупредительных ремонтов машин, техники и оборудования. В-третьих, налаживание связи головного офиса с участками, а также стимулирование труда персонала. Данные мероприятия позволят не только увеличить эффективность работы компании в целом, но и могут рассматриваться как универсальные для предприятий, работающих в данной сфере.